PENGARUH PEMBELAJARAN KOOPERATIF DALAM PENGEMBANGAN KECERDASAN INTERPERSONAL SISWA PADA PELAJARAN MATEMATIKA DI MADRASAH - Nurul Komar; Taufik Taufik (STIT AL-AMIN KREO TANGERANG, 2021)
This study aims to determine and analyze the effect of cooperative learning on the development of students' interpersonal intelligence in madrasa, cooperative learning is carried out in the learning process of mathematics subjects. In this study, we want to examine and find out the right learning method to be used in learning mathematics in the classroom. This study uses correlation and regression analysis using a sample of 75 people. The sample used in the study was students at Madrasah Tsanawiyah Negeri 13 Jakarta. From the results of the study, it was found that cooperative learning with the jigsaw method and Group Investigation (group investigation) is more dominant and has a significant effect when compared to the STAD and TGT methods in the mathematics learning process in madrasas.